Correlação entre termografia infravermelha e marcadores fisiológicos para controle de cargas de treino em atletas de basquetebol - Araújo, Valbério Candido de (2018)
Infrared thermography (IT) has been applied among athletes as an indicator of internal training load, with the advantages of being simple and non-invasive. However, its consistency has not yet been determined. The objective of this study was to compare the changes in skin temperature, through IT, induced by an exercise session (acute study - AS) and throughout a training season (chronic study - CS) with changes in physiological measures of inflammation, oxidative stress, muscle damage, autonomic modulation and referred sensation. The participants were 17 athletes (20.9 ± 3.2 years) and 13 athletes (20.4 ± 2.8 years), all of whom were from a semiprofessional basketball team. In AS, the athletes performed a circuit composed of 8 exercises with characteristics of strength, power, eccentricity and speed. Before the circuit, immediately after and after 2, 4, 24 and 48 hours, they were submitted to measurements of heart rate variability (HRV), blood samples for analysis of muscle damage markers creatine kinase (CK), lactate dehydrogenase (LDH), ultra-sensitive C-reactive protein (CRP-us), total antioxidant activity (TAA), malondialdehyde (MDA), and TI. The EC lasted 12 weeks, consisting of technical / tactical / physical training and competitive games. The AS assessments were replicated in the CS every four weeks, plus psychometric tests (mood state, overtraining questionnaire). To analyze the data, we used the ANOVA test for repeated measures and Spearman correlation. The physical exercises of the AD promoted increase of CK and / or LDH for up to 48h post training, but without alteration for PCR-us, CAT and MDA. There was also parasympathetic reduction (RMSSD) and sympathetic increase, but only at the moment immediately after training. At the same time, the whole body temperature (WBT), which was composed by the mean of all evaluated areas, showed a significant increase from 31.3 ± 0.4 ° C, to 32.0 ± 0.5 ° C 2h post training (PT) and 4h PT (31.5 ± 0.5 ° C), reducing PT 24h (30.7 ± 0.5 ° C) and returning values similar to the initial 48h PT (31.4 ± 0.6 ° W). These changes in WBT correlated with PT-CR immediately PT (r = -0.505, p = 0.039), CAT 4h PT (r = -0.533, p = 0.027), MDA immediately PT (r = -0.559, p = 0.020) and RMSSD 24h PT (r = -0.487, p = 0.048). In the EC, muscle damage was observed in the 4th and 8th weeks of training, but the other variables remained without indicating oxidative stress, autonomic disturbance or mood state. Meanwhile, TICI values started at 31.3 ± 0.4 ° C, rising to 31.1 ± 0.5 ° C 4 weeks later and increasing significantly to 31.7 ± 0.4 ° C with 8 weeks of training. The body temperature segmented by body temperature maintained similar behavior to the whole body, with a significant increase in the 8th week of the season. Correlations of TICI with CK (r = -0.487, p = 0.048) and yield (r = -0.487, p = 0.048) with 8 weeks of training and with vigor (r = -0.487, p = 0.048) after 12 weeks. It is concluded that TI data do not consistently follow the physiological indicators of muscle damage, oxidative stress, systemic inflammation, heart rate variability and mood states, either in EA or in CD, but because of some body follow-up, with one or another physiological variable at isolated moments.